West Nile virus outbreak in Israel in 2015: phylogenetic and geographic characterization in humans and mosquitoes. (December 2017) - Lustig, Y.; Kaufman, Z.; Mannasse, B.; Koren, R.; Katz-Likvornik, S.; Orshan, L.; Glatman-Freedman, A.; Mendelson, E.
Abstract: Objectives: West Nile Virus (WNV) is endemic in Israel and was responsible for several outbreaks in the past 16 years. The aim of the present study was to investigate the spatial distribution of WNV acute infections from an outbreak that occurred in 2015 in Israel and report the molecular and geographic characterization of WNV isolates from human cases and mosquito pools obtained during this outbreak. Methods: Using a geographical layer comprising 51 continuous areas of Israel, the number of WNV infection cases per 100 000 people in each area and the locations of WNV-infected mosquitoes in 2015 were analysed. Sequencing and phylogenetic analyses followed by geographic localization were performed on 13 WNV human isolates and 19 WNV-infected mosquito pools. Results: Substantial geographical variation in the prevalence of acute WNV in patients in Israel was found and an overall correlation with WNV-infected mosquitoes. All human patients sequenced were infected only with the Mediterranean subtype of WNV Lineage 1 and resided primarily in the coastal regions in central Israel. In contrast, mosquitoes were infected with both the Mediterranean and Eastern European subtypes of WNV lineage 1; however, only the Mediterranean subtype was found in mosquitoes from the coastal region in central Israel. Conclusion: These results demonstrate differential geographic dispersion in Israel of the two WNV subtypes and may also point to a differential pattern of human infections. As a geographical bridge between Europe, Asia and Africa, analysis of WNV circulation in humans and mosquitoes in Israel provides information relevant to WNV infections in Eurasia.